1970
DOI: 10.3329/jdmc.v20i1.8589
|View full text |Cite
|
Sign up to set email alerts
|

Fahr’s Disease: A Rare Neurodegenerative Disorder in Children

Abstract: A case of Fahr’s disease in reported in a 2 year 9 month old male child presented with developmental delay and seizure. The CT scan of brain showed multiple symmetric calcifications in the basal ganglia, thalamus, and subcortical white matter of cerebral and cerebellar areas. No underlying cause for the bilateral calcification was found. This rare case of Fahr’s disease in a child, which has never been reported in Bangladeshi literature, has been brought out to highlight this unusual condition. Key words: Fahr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The present study showed the increased percentage of MRSA in hospital-acquired, ICUs, burn wards. The results are accorded with reference to Rahman et al, and Scerri et al, [26][27]. The increased resistance could be due to insignificant selfmedication, untimely and arbitrary use of antibiotics.…”
Section: Resultssupporting
confidence: 86%
“…The present study showed the increased percentage of MRSA in hospital-acquired, ICUs, burn wards. The results are accorded with reference to Rahman et al, and Scerri et al, [26][27]. The increased resistance could be due to insignificant selfmedication, untimely and arbitrary use of antibiotics.…”
Section: Resultssupporting
confidence: 86%